2022
DOI: 10.1186/s12872-022-03014-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C alleviates LPS-induced myocardial injury by inhibiting pyroptosis via the ROS-AKT/mTOR signalling pathway

Abstract: Background The efficacy of vitamin C in sepsis remains controversial. Whether vitamin C can alleviate lipopolysaccharide (LPS)-induced myocardial injury by inhibiting pyroptosis has not been studied. This study aimed to evaluate the effects of vitamin C on LPS-induced myocardial injury in vitro. Methods H9C2 cells were treated with indicated concentrations of LPS, and the cell viability was then assessed by CCK-8 assay. The levels of lactate dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Meanwhile, blocking the PI3K/AKT/mTOR signaling pathway during sepsis triggers autophagy and blocks apoptosis [7]. A recent study showed that VC could protect against SIMI by inhibiting AKT/mTOR pathway activation and pyrodeath [81]. The present study discovered that the levels of p-AKT, p-PI3K and p-mTOR were elevated in SIMI rats, whereas high-dose VC reduced their phosphorylation levels, indicating that high-dose VC protected SIMI in rats by the inhibition of PI3K/AKT/mTOR signaling pathway, consistent with the latter view.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, blocking the PI3K/AKT/mTOR signaling pathway during sepsis triggers autophagy and blocks apoptosis [7]. A recent study showed that VC could protect against SIMI by inhibiting AKT/mTOR pathway activation and pyrodeath [81]. The present study discovered that the levels of p-AKT, p-PI3K and p-mTOR were elevated in SIMI rats, whereas high-dose VC reduced their phosphorylation levels, indicating that high-dose VC protected SIMI in rats by the inhibition of PI3K/AKT/mTOR signaling pathway, consistent with the latter view.…”
Section: Discussionmentioning
confidence: 99%